A Rare Case of Respiratory Disorders Associated with Two Autosomal Recessive Diseases and Male Infertility. Issue 1 (March 2013) - Mendeluk, Gabriela Ruth; Costa, Sergio López; Scigliano, Sergio; Menga, Guillermo; Demiceu, Sergio; Palaoro, Luis Alberto
The study of nasal ciliary beat frequency (CBF) and ultrastructure may contribute to the understanding of pathognomonic cases of male infertility associated with defects in sperm motility. This study was designed to report a particular case of male infertility, characterized by the association of two respiratory autosomal recessive genetic diseases (alpha-1-antitrypsin deficiency [AAT-D] and primary ciliary dyskinesia [PCD]). A 39-year-old patient with complete sperm immotility, AAT-D, and bronchiectasis was studied in the Laboratory of Male Fertility, the Department of Urology, the Respiratory Center of a Pediatric Hospital, and in the Department of Clinical Medicine of a Rehabilitation Respiratory Hospital. Family history, physical examination, hormonal analysis, microbial assays, semen analysis, nasal ciliary function, and structure study by digital high-speed video photography and transmission electron microscopy are described. A noninvasive nasal biopsy to retrieve ciliated epithelium lining the inferior surface of the inferior nasal turbinates was performed and CBF was determined. Beat pattern was slightly curved and rigid, not wide, and metacronic in all the observed fields analyzed. CBF was 8.2 Hz in average (reference value, 10–15 Hz) Ultrastructural assay revealed absence of the inner dynein arms in 97% of the cilia observed. The final infertility accurate diagnosis was achieved by the study of nasal CBF and ultrastructure contributing to the patient health management and genetic counseling while deciding fatherhood. Beyond this particular case, the present report may open a new field of studies in male infertility, mainly in cases of asthenozoospermia.